A method for single pair mating in an obligate parasitic nematode. Issue 2 (February 2018) - Sargison, Neil D.; Redman, Elizabeth; Morrison, Alison A.; Bartley, David J.; Jackson, Frank; Naghra-van Gijzel, Hardeep; Holroyd, Nancy; Berriman, Matthew; Cotton, James A.; Gilleard, John S.
Graphical abstract: Highlights: A novel method to achieve single pair mating in an obligate nematode parasite. Comprehensive validation using a variety of molecular and genomic tools. Production of inbred lines for genome assembly and genetic crossing experiments. Pertinent in the study of anthelmintic resistance in nematode parasites of humans and livestock. Abstract: Parasitic nematode species have extremely high levels of genetic diversity, presenting a number of experimental challenges for genomic and genetic work. Consequently, there is a need to develop inbred laboratory strains with reduced levels of polymorphism. The most efficient approach to inbred line development is single pair mating, but this is challenging for obligate parasites where the adult sexual reproductive stages are inside the host, and thus difficult to experimentally manipulate. This paper describes a successful approach to single pair mating of a parasitic nematode, Haemonchus contortus . The method allows for polyandrous mating behaviour and involves the surgical transplantation of a single adult male worm with multiple immature adult females directly into the sheep abomasum. We used a panel of microsatellite markers to monitor and validate the single pair mating crosses and to ensure that the genotypes of progeny and subsequent filial generations were consistent with those expected from a mating between a single female parent of known genotype and a single male parent of unknown genotype. We have established two inbred lines that both show a significant overall reduction in genetic diversity based on microsatellite genotyping and genome-wide single nucleotide polymorphism. There was an approximately 50% reduction in heterozygous SNP sites across the genome in the MHco3.N1 line compared with the MoHco3(ISE) parental strain. The MHco3.N1 inbred line has subsequently been used to provide DNA template for whole genome sequencing of H. contortus . This work provides proof of concept and methodologies for forward genetic analysis of obligate parasitic nematodes.